Parametric evaluation of the performance characteristics of tight moored wave energy converters - Mavrakos, SA; Katsaounis, GM (2005)
The paper aims at presenting a numerical model to predict performance characteristics of tight moored vertical axisymmetric wave energy converters that are allowed to move in heave, pitch and sway modes of motion. The hydrodynamic characteristics (exciting wave forces, hydrodynamic parameters) of the floats are evaluated using a linearized diffraction - radiation method of analysis that is suited for the type of bodies under consideration. According to this method matched axisymmetric eigenfunction expansions of the velocity potentials in properly defined fluid regions around the body are introduced to solve the respective diffraction and radiation problems and to calculate the floats' hydrodynamic characteristics in the frequency domain. Based on these characteristics, the retardation forcing terms are calculated, which account for the memory effects of the motion. In this procedure, the coupling terms between the different modes of motion are properly formulated and taken into account The floating WEC is connected to an underwater piston that feeds a hydraulic system with pressurized fluid. Numerical results showing parametrically the performance characteristics in terms of the expected power production for several types of floats that are exposed to the wave climate conditions commonly encountered in the Mediterranean area are presented and discussed Copyright © 2005 by ASME.